Electronic Parking Control Systems - Marma, A.; Žilys, M.; Eidukas, D.; Valinevičius, A. (Elektronika ir Elektrotechnika, 2007)
Problems in the big parking lots near big people concentration places were researched. To control processes in parking lots electronic control systems are needed. These systems was analysed, systems architecture and their hierarchy structured. To ensure best performance in the multi floor parking lot with 2500 parking places electronic systems were implemented: parking guidance, traffic jams detection and control, intelligent administration and handling and emergency situation control. All these systems were developed, installed, tuned, tested and experimental data collected for modelling. To model these systems over 500000 measurements were done during experiment. To find a phenomenon appearing before traffic jam is formed in the parking-lot, recognize and forecast traffic jams in the parking-lot model with neural network using Levenberg-Marquardt optimization was done. Experimental and modelling results showed advantages of the Electronic Parking Control Systems. Ill. 15, bibl. 6 (in English; summaries in English, Russian and Lithuanian).